The Effect Of Price And Product Quality On Repurchase Interest In Ud Kunyahan Medan Potato Chips - Siti Azura; Dian Septiana Sari; Roro Rian Agustin (Journal of Management, Economic, and Accounting, 2026)
This study aims to examine the effect of price and product quality on repurchase intention on UD Kunyahan Medan potato chips. The number of respondents is 40 customers from UD Kunyahan Medan who buy directly through the owner. Quantitative research method with multiple linear regression data analysis techniques, The data collection tools are observation, documentation and interviews. The data processing tool is SPSS Version 23.0. The results show that Price has a significance value of 0.010 <0.05 and a calculated value of 2.728> t table 2.026192, then H₀ is rejected and H₁ is accepted. Thus, it can be concluded that Price has a positive and significant effect partially on Repurchase Intention. Product Quality has a significance value of 0.001 <0.05 and a calculated t value of 3.522> t table 2.026192, then H₀ is rejected and H₂ is accepted. Thus, it can be concluded that Product Quality has a positive and significant partial effect on Repurchase Intention. The calculated F value is 28.060 > F table 2.85 with a significance value of 0.000 < 0.05. Thus, H₀ is rejected and H₃ is accepted. This shows that simultaneously, the variables Price and Product Quality have a significant effect on Repurchase Intention.